2016
DOI: 10.1080/10286608.2016.1202931
|View full text |Cite
|
Sign up to set email alerts
|

A systems approach to flood vulnerability

Abstract: For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 18 publications
0
22
0
1
Order By: Relevance
“…Balica, Douben, and Wright (2009) develop Flood Vulnerability Indicators which include physical and social vulnerability. Beevers, Walker, and Strathie (2016) and Adeyeye and Emmitt (2017) combine both physical and social systems within their methodologies. Furthermore, strategic research starts to emerge at this scale (see e.g., Restemeyer, Woltjer, and van den Brink 2015).…”
Section: Conceptual/ Theoreticalmentioning
confidence: 99%
See 1 more Smart Citation
“…Balica, Douben, and Wright (2009) develop Flood Vulnerability Indicators which include physical and social vulnerability. Beevers, Walker, and Strathie (2016) and Adeyeye and Emmitt (2017) combine both physical and social systems within their methodologies. Furthermore, strategic research starts to emerge at this scale (see e.g., Restemeyer, Woltjer, and van den Brink 2015).…”
Section: Conceptual/ Theoreticalmentioning
confidence: 99%
“…Whilst the study focuses on individual resilience, it explores the relationship between the individual and varying spatial scales of the city system. Aside from connecting the interdependencies of scales in the social system, Beevers, Walker, and Strathie (2016) and Adeyeye and Emmitt (2017) attempt to combine socio-technical interactions for a more holistic understanding of flood resilience at multiple scales.…”
Section: Conceptual/ Theoreticalmentioning
confidence: 99%
“…More explicitly managing connections between infrastructure systems can also reduce the pressure on vulnerable points in the system. Interdependence between infrastructure systems has become a major research area in the last 30 years, and by exploiting the capacity between systems we could increase the potential for cascading failures through the system; amplifying small disruptions into large disruptions (Balica, Douben, & Wright, ; Beevers, Walker, & Strathie, ; da Silva, Kernaghan, & Luque, ; Eusgeld, Nan, & Dietz, ; Ouyang & Dueñas‐Osorio, ; Peerenboom & Fisher, ; Pregnolato et al, ). For example, hydrological model simulations in Malmö, Sweden, have also shown that the efficiency of a BGI system in mitigating flooding can be strongly limited if implemented in an area with a hydraulically overloaded piped sewer network (Haghighatafshar et al, ).…”
Section: Opportunities Through Interoperabilitymentioning
confidence: 99%
“…La catégorie du médical couvre des domaines de travail qui portent sur le corps humain [14] et un système de médication à domicile [23]. Le domaine de travail de la catégorie d'automatisation est un appareil photo [25], le domaine de travail de la catégorie des désastres naturels est une ville en cas d'inondation [2], le domaine de travail de la catégorie du jeu est le football européen [18], le domaine de travail de la catégorie du militaire est un navire de guerre [3] et le domaine de travail de la catégorie des ressources humaines est la supervision d'équipes [29]. Functional purpose [1, 2, 4, 6, 7, 10, 12, 15, 16, 18-20, 22, 23, 25, 29, 31, 36, 37, 43-45] Functional goals [17] General purposes [28] Highest level goals [3] Overall purpose [21] Purposes [14] Abstract function [4, 6, 7, 10, 12, 15-17, 22, 25, 28, 29, 43-45] Abstract function and priority measures [1] Abstract purpose [19] Balances [14] Generic control functions [21] Priorities and constraints [3] Values & priority measures; Priorities/values [2,18,20,23,36,37] Priority measures [31] Generalized functions [3,4,6,7,10,12,15,16,22,25,29,[43][44][45] General functions…”
Section: Domaines De Travailunclassified